2019
DOI: 10.1126/scitranslmed.aav5264
|View full text |Cite
|
Sign up to set email alerts
|

Human genetics and neuropathology suggest a link between miR-218 and amyotrophic lateral sclerosis pathophysiology

Abstract: Motor neuron–specific microRNA-218 (miR-218) has recently received attention because of its roles in mouse development. However, miR-218 relevance to human motor neuron disease was not yet explored. Here, we demonstrate by neuropathology that miR-218 is abundant in healthy human motor neurons. However, in amyotrophic lateral sclerosis (ALS) motor neurons, miR-218 is down-regulated and its mRNA targets are reciprocally up-regulated (derepressed). We further identify the potassium channel Kv10.1 as a new miR-218… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 71 publications
2
53
0
Order By: Relevance
“…Mir-218-5p is a microRNA found to be expressed in 20 vertebrate species (http://www.mirbase.org/). It has been implicated in tumorigenesis and cancer progression of different tumor entities (reviewed in [50]), as well as its role in the motor neuron development has recently been discovered [51,52]. However, regarding the role of miR-218 in chondrogenesis, the published literature is very limited and so far presents somewhat contradicting claims.…”
Section: Discussionmentioning
confidence: 99%
“…Mir-218-5p is a microRNA found to be expressed in 20 vertebrate species (http://www.mirbase.org/). It has been implicated in tumorigenesis and cancer progression of different tumor entities (reviewed in [50]), as well as its role in the motor neuron development has recently been discovered [51,52]. However, regarding the role of miR-218 in chondrogenesis, the published literature is very limited and so far presents somewhat contradicting claims.…”
Section: Discussionmentioning
confidence: 99%
“…In this study the authors identified the potassium channel KV10.1 as a novel miR-218 target that regulates neuronal activity. From sequencing thousands of ALS genomes, they also identified six rare miR-218-2 gene variants that failed to regulate neuronal activity due to reduced processing by DICER, further highlighting the importance of miR-218 in MNs ( Reichenstein et al, 2019 ).…”
Section: Neuronal Subtype Determination and Functionmentioning
confidence: 99%
“…To elucidate the tissue source of miR-181 we revisited previously reported Nanostring data 25 . miR-181a-5p is the ninth most abundant miRNA in laser capture micro-dissected human motor neurons of ALS patients and is also fairly abundant in the CNS in general 26 .…”
Section: Resultsmentioning
confidence: 99%